ANALISIS KESIAPAN GURU KIMIA DALAM MENGIMPLEMENTASIKAN MODUL AJAR BERBASIS KURIKULUM MERDEKA - Rahmi, Chusnur (Lantanida Journal, 2024)
In dealing with the Merdeka Curriculum revisions, teachers must not only be capable and competent in developing instructional modules that match the needs of students. Teachers must also be able to apply them effectively during the learning process. This offers a big difficulty to teachers. This study intends to investigate the preparation of chemistry teachers and the challenges they confront when adopting teaching modules based on the Merdeka Curriculum. In this instance, numerous attempts can be taken to improve chemistry teachers' readiness to confront the issues they face. This form of research is descriptive and takes a qualitative approach. The data collecting subjects are three chemistry teachers from a senior high school in Banda Aceh City. The research data was obtained using semi-structured interviews. The data analysis technique uses the Miles and Huberman method. According to the study's findings, chemistry teachers are unprepared to adopt Merdeka Curriculum-based teaching modules. Teachers recognize the Merdeka Curriculum's essential concepts but lack confidence in constructing teaching modules on their own. Chemistry teachers face challenges in implementing teaching modules based on the Merdeka Curriculum, including a lack of training provided by schools to enhance teachers' understanding and skills regarding the structure and implementation of the independent curriculum in the chemistry learning process. To overcome this issue, schools could organize Merdeka Curriculum training or workshops to help teachers enhance their skills. Furthermore, the implementation of the Merdeka Curriculum demands efforts for coordination among teachers, school principals, and the school's educational office.